Restoration of the Oral Microbiota After Surgery for Head and Neck Squamous Cell Carcinoma Is Associated With Patient Outcomes - Chan, Jason Y. K.; Ng, Cherrie W. K.; Lan, Linlin; Fung, Sherwood; Li, Jing-Woei; Cai, Liuyang; Lei, Pu; Mou, Qianqian; Meehan, Katie; Lau, Eric H. L.; Yeung, Zenon; Chan, K. C. Allen; et al. (Frontiers in Oncology, 2021)
Objective: To evaluate the dynamics of the oral microbiome and associated patient outcomes following treatment of HNSCC. Materials and methods: This was a prospective cohort study at a tertiary academic center in Hong Kong SAR of patients with head and neck squamous cell carcinoma evaluating the oral microbiome in pre- and post-surgery oral rinses (at 1, 3 and 6 months) with 16S rRNA gene V3-V4 amplicon sequencing. Results: Seventy-six HNSCC patients were evaluated. There was a significantly depressed alpha diversities of oral microbial communities observed in HNSCC oral rinse samples within the first 6 months post-surgery when compared to pre-surgery or healthy controls. Distant clustering between pre- and post-surgery was also observed (p < 0.022). Following treatment eight oral bacterial genera showed a trend towards the restoration in the relative abundances that approximate healthy persons. In evaluating patient outcomes, the decreased relative abundance of three periodontal bacteria (Capnocytophaga, Prevotella 7, Leptotrichia) and the increased relative abundance of two commensal bacteria (Streptococcus, Rothia) at 6 months post-surgery compared to pre-surgery showed a better 3-year disease-specific survival (a cutoff of Kaplan-Meier survival curve test p < 0.3 at 36 months). In particular, the post-surgery restoration of Prevotella 7 was statistically significant in the surveyed patients (survival rate of 84% vs 56% at 36 months, p = 0.0065). Conclusions: Oral microbiome dysbiosis associated with HNSCC is dynamic. These dynamics of the oral microbiome post-surgery are also associated with patient treatment and outcomes, and may serve as potential biomarkers for patient management in HNSCC.